2004
DOI: 10.1097/01.blo.0000126308.72205.be
|View full text |Cite
|
Sign up to set email alerts
|

Insufficiency Fracture of the Body of the Calcaneus in Elderly Patients with Osteoporosis

Abstract: Two cases of insufficiency fracture of the body of the calcaneus are presented to show its clinical presentation and diagnosis. It often is overlooked as a cause of pain in the ankle region. Both patients were elderly women with pain developing at the lateral aspect of the hindfoot in the absence of significant trauma. Physical examination was significant for marked tenderness at the superolateral aspect of the calcaneus. These clinical features suggested the diagnosis, which was confirmed by radionuclide bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…It is unknown why all thirteen patients in both the present report and the reports by Ito et al 24 and by Alonso-Bartolome 25 were female. In part, it may be because osteoporosis occurs more frequently in females, and nearly 80% of the candidates for joint replacement in our hospital are female.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…It is unknown why all thirteen patients in both the present report and the reports by Ito et al 24 and by Alonso-Bartolome 25 were female. In part, it may be because osteoporosis occurs more frequently in females, and nearly 80% of the candidates for joint replacement in our hospital are female.…”
Section: Discussionmentioning
confidence: 52%
“…Calcaneal insufficiency fractures occur in bones having less than normal elastic resistance to compression and stretching. They occur in elderly individuals with osteoporosis without any antecedent trauma or overuse 24,25 and are not commonly recognized [24][25][26][27][28][29][30] . The cases of two patients reported by Ito et al 24 , the cases of six patients reported by Alonso-Bartolome et al 25 , and the five patients in the present report are the best examples in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this case, the clinical signs were mild pain in the medial aspect of the ankle, which was confirmed by an MRI. [11,12] The treatment of an insufficiency fracture depends on the clinical presentation and whether the fracture is complete or incomplete. Treatment options are conservative treatment, a splint or a cast, and an operation such as internal fixation.…”
Section: Discussionmentioning
confidence: 99%
“…1). Therefore, it gives a clue to accompanying ligament lesions and grades the lesion at the distal tibiofibular and ankle joint as being stable or unstable (2)(3)(4)(5)(6)(7). In case of supination-adduction trauma (Weber A type), the presence of an oblique (push off) fracture of the medial malleolus includes a major lateral lesion.…”
Section: Discussionmentioning
confidence: 99%